Association between assesment and missed pain treatment among patients with headache pain presenting to the emergency department - Singh, Gurjeet (2020)
Background Pain assessment and management has been widely practiced in emergency departments all over the world. As proper pain management is directly related to improvement in patient satisfaction, health care officers have to be effectively dealt with pain related chief complaints daily. A common chief complaint of patients presenting to the emergency departments all over the world including Malaysia is headache. The aim in this study is to analyze the assessment and management of headache pain at the emergency department in Hospital Universiti Sains Malaysia and the factors that were influencing them. Methods The factors associated with missed pain assessment and treatment among patients with headache pain presenting to the emergency department were investigated. A cross sectional retrospective observational study was performed from December 2017 to May 2018 among all patients with headache presenting to the emergency department of Hospital University Sains Malaysia (HUSM). A total of 94 patients were enrolled in this study and 77 patients met the inclusive criteria. Results There was a statistically significant association (p-value<0.05) between pain reassessment and also the triage zone (x2 =6.858) and patient’s arrival time (x2 =5.773). Together with that a significant association (p-value<0.05) between missed pain treatment and triage zone, and patient’s arrival time was identified. The chi square value (x2) for triage zone and patient arrival were 7.428 and 4.807 each. Whereas, there was no significant association between pain treatment and attending physician Conclusion Triage zone and arrival time of patients are the factors influencing miss assessment and management of pain among patients with headache presenting to ED. A proper action and more intervention studies are warranted in order to overcome above mentioned issues and optimize pain management for headache pain.